Design of a Novel Frequency-Coded Chipless RFID Tag - Yuan Gao; Mahboobeh Mahmoodi; Reza Zoughi (IEEE Open Journal of Instrumentation and Measurement, 2022)
Chipless radio frequency identification (RFID) is a low-cost RFID solution that has the potential to replace traditional barcodes in short-range applications. In this paper, a novel frequency-coded chipless RFID tag is designed at Ku-band (12.4–18 GHz). Compared to previous designs, the proposed tag has a more compact design by multiplexing one tag antenna for both transmitting and receiving purposes. In addition, the tag is designed on a substrate with ground plane, which reduces the undesired effect of the background detuning. To demonstrate the performance of the proposed chipless RFID tag, four 3-bit tags are designed in simulation, with having two of them manufactured and tested. Simulations and measurements are performed for codes of 000 and 111, and the results verify the validity of the proposed design. Finally, the sensitivity of the tag response to fabrication errors and orientation are discussed and demonstrated with simulations.